Sertifikasi dan Kompetensi Pelaut sebagai Faktor Penentu Kinerja Perusahaan Pelayaran - Saputra, Datep Purwa; Pangibulan, Pangibulan; Soekirman, Atong; Suseno, Bambang Dwi; Nelmida, Nelmida (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2026)
ABSTRACT Some shipping companies in Indonesia are still not optimal in using Standard Operating Procedures according to the International Safety Management Code and are not updated regularly according to changes that occur in the company's operations. In addition, the lack of good seamanship in getting sufficient training in terms of basic maritime knowledge, practical skills. This study aims to analyze the influence of crew certification and seafarer skills on the operational performance of several shipping companies with standard operating procedures as intervening variables. This study uses the Structural Equation Model method based on Partial Least Squares and uses a sample of 86 crew members from three shipping companies. The results show that crew certification influences the operational performance of shipping companies, while good seamanship does not. Additionally, SOP does not influence the operational performance of shipping companies, though good seamanship does affect SOP. SOP also influences the operational performance of shipping companies, but it does not mediate the relationship between crew certification and operational performance, nor does it mediate the relationship between good seamanship and operational performance of shipping companies.